Hubungan Persepsi Pasien Tentang Empati Perawat Dengan Kepuasaan Pasien Di Ruang Rawat Inap RSUD SlemanYogyakarta - Nur Hafni Hasim; Induniasih Induniasih; Fajarina Lathu Asmarani (Poltekkes Kemenkes Yogyakarta, 2018)
The patient's perception of the nurse's empathy attitude is a personal view of something which is a process of realizing something object or condition through the use of all sensory devices. Patient perception is important because perception is often used to assess the quality or quality of health services. The level of patient satisfaction which is the output of this perception can be used to evaluate service quality. The purpose of knowing the relationship between patients' perceptions of empathy nurses and patient satisfaction in Class III hospitalization in Sleman Hospital. The method in this study is a non-analytic descriptive experiment with a cross-sectional approach. The population in this study were 324 patients with 147 samples selected based on accidental sampling with consideration of inclusion and exclusion criteria. The research instrument was a questionnaire. Analyzed by Spearman rank analysis. The results showed that patients' perceptions of empathy nurses were in a good category (75.6%). Patient satisfaction about empathy nurses was in the satisfied category (86.4%). The results of the Spearman Rank test show the correlation coefficient (rho) of 0.688 with significant value (?) of 0,000, smaller than the significant level of 0.05 (? <0.05). Conclusion: There is a relationship between patient perceptions about empathy for nurses and patient satisfaction.